(untitled) (IASH Indian Journal of Arid Horticulture, 2026)
A field experiment was conducted during the year 2023-24 on Chandra variety of jackfruit, at the Instructional Farm, Department of Fruit Science, College of Horticulture and Forestry, Jhalawar. The result indicated that the application of treatment T1 (soil under banyan tree canopy) was the most effective in increasing the soil porosity (47.84%) and it reduced the soil pH (7.14), electrical conductivity (0.22 dS m-1), bulk density (1.13 g cm-3) and particle density (2.32 g cm-3). Thus, the T1 (soil under banyan tree canopy) treatment significantly improved all soil parameters in orchard of jackfruit